Pap test for Screening of Carcinoma of Cervix: Analysis of one Hundred Patients (TAJ: Journal of Teachers Association, 2009)
During the period of July-2005 to June 2006 a total 100 women under went pap testing in Dinajpur, Bangladesh. The aim of the study was to observe the pattern of histological changes in cervical epithelia among sexually active women in Dinajpur. Results of Pap's test revealed inflammatory changes in 69%, cases, inflammatory with squamous metaplasia in 23% cases, normal 6%, atypia 1% & dyskaryosis in 1% case.   doi: 10.3329/taj.v19i2.3155 TAJ 2006; 19(2): 76-80